Comparative Analysis of Ethylene/Diene Copolymerization and Ethylene/Propylene/Diene Terpolymerization Using Ansa-Zirconocene Catalyst with Alkylaluminum/Borate Activator: The Effect of Conjugated and Nonconjugated Dienes on Catalytic Behavior and Polymer Microstructure - Amjad Ali; Muhammad Khurram Tufail; Muhammad Imran Jamil; Waleed Yaseen; Nafees Iqbal; Munir Hussain; Asad Ali; Tariq Aziz; Zhiqiang Fan; Li Guo (Molecules, 2021)
The copolymerization of ethylene‒diene conjugates (butadiene (BD), isoprene (IP) and nonconjugates (5-ethylidene-2-norbornene (ENB), vinyl norbornene VNB, 4-vinylcyclohexene (VCH) and 1, 4-hexadiene (HD)), and terpolymerization of ethylene-propylene-diene conjugates (BD, IP) and nonconjugates (ENB, VNB, VCH and HD) using two traditional catalysts of C2-symmetric metallocene—silylene-bridged rac-Me2Si(2-Me-4-Ph-Ind)2ZrCl2 (complex A) and ethylene-bridged rac-Et(Ind)2ZrCl2 (complex B)—with a [Ph3C][B(C6F5)4] borate/TIBA co-catalyst, were intensively studied. Compared to that in the copolymerization of ethylene diene, the catalytic activity was more significant in E/P/diene terpolymerization. We obtained a maximum yield of both metallocene catalysts with conjugated diene between 3.00 × 106 g/molMt·h and 5.00 × 106 g/molMt·h. ENB had the highest deactivation impact on complex A, and HD had the most substantial deactivation effect on complex B. A 1H NMR study suggests that dienes were incorporated into the co/ter polymers’ backbone through regioselectivity. ENB and VNB, inserted by the edo double bond, left the ethylidene double bond intact, so VCH had an exo double bond. Complex A’s methyl and phenyl groups rendered it structurally stable and exhibited a dihedral angle greater than that of complex B, resulting in 1, 2 isoprene insertion higher than 1, 4 isoprene that is usually incapable of polymerization coordination. High efficiency in terms of co- and ter- monomer incorporation with higher molecular weight was found for complex 1. The rate of incorporation of ethylene and propylene in the terpolymer backbone structure may also be altered by the conjugated and nonconjugated dienes. 13C-NMR, 1H-NMR, and GPC techniques were used to characterize the polymers obtained.